Perbudakan di Era Modern: Prison Labor dalam Perdagangan Global - Maya Indah Bofa (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
The 1926 Slavery Convention signed at Geneva called states to end every act of trade or transport in slaves and ensure that forced labor, where practiced, should not develop into ‘conditions analogous to slavery’. Although slavery is already considered illegal, does it really ends? This research is conducted by library research and using the concept of modern slavery and global capitalism to explain prison labor as forced labor is contributing in global trade. This research finds that slavery is still alive and well until today. Although exporting goods made by prison labor is illegal under international law, products made by prisoners are still found in the global supply chain. Prisons are a reflection of the Third World countries since prisoners are not protected by minimum wage laws. They are also hindered from the right to organize and collectively bargain. Furthermore, since prisons are run like companies, but, unlike companies, prisons do not enforce labour law, this enables corporations making money from imprisoned human beings through prison labour. Keywords: global capitalism; human rights; modern slavery; prison labor.